2016
DOI: 10.1179/1476830514y.0000000142
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid and autism: What do we know?

Abstract: Autism spectrum disorders (ASD) consist in a range of neurodevelopmental conditions that share common features with autism, such as impairments in communication and social interaction, repetitive behaviors, stereotypies, and a limited repertoire of interests and activities. Some studies have reported that folic acid supplementation could be associated with a higher incidence of autism, and therefore, we aimed to conduct a systematic review of studies involving relationships between this molecule and ASD. The M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 28 publications
1
31
0
3
Order By: Relevance
“…These are grouped by general function in Fig 9. They include compounds related to oxidative stress and folate/methionine/homocysteine metabolism which play key roles in autism [192][193][194][195] as do cholesterol and fatty acid metabolism [196][197][198][199] or inflammation [200][201][202][203]..…”
Section: Other Endogenous Compounds Targeting Autism Genesmentioning
confidence: 99%
“…These are grouped by general function in Fig 9. They include compounds related to oxidative stress and folate/methionine/homocysteine metabolism which play key roles in autism [192][193][194][195] as do cholesterol and fatty acid metabolism [196][197][198][199] or inflammation [200][201][202][203]..…”
Section: Other Endogenous Compounds Targeting Autism Genesmentioning
confidence: 99%
“…To date, several studies report the programing effects of maternal FA supplementation on the offspring's health, mainly regarding autism (Castro et al 2014), asthma, insulin resistance, and cancer (see Burdge & Lillycrop (2012) for a review). Results of studies of fetal programing of cancer by high FA exposure are somewhat conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that periconceptional folic acid supplementation, depending on timing and dose, could be associated with a higher incidence of autism. But nevertheless, a recent meta-analysis shows that the few and contradictory studies present inconsistent conclusions, and epidemiological associations are not reproduced in most of the other types of studies [294]. On the other hand, a well-controlled epidemiological study including a sample of 85,176 children disconfirms this claim and reports a lower incidence of ASD in children whose mothers received prenatal folic acid supplementation around the time of conception (0.10%) compared with those unexposed to folic acid (0.21%) [295].…”
Section: Autism -Paradigms Recent Research and Clinical Applicationsmentioning
confidence: 99%
“…Also, some studies have reported lower folate levels in patients with ASD [299,300] and high levels of homocysteine [299,301]. Folic acid supplementation may have a certain role in the treatment of children with autism, and this treatment also improved the concentrations of folic acid, homocysteine, and normalized glutathione redox metabolism [302]; but the effects of folate-enhancing interventions on the clinical symptoms have yet to be confirmed [294].…”
Section: Autism -Paradigms Recent Research and Clinical Applicationsmentioning
confidence: 99%